Effect of Digital Intervention on Chemotherapy Adherence: A Systematic Review - Juniari, Ni Made; Sukartini, Tintin; Nihayati, Hanik Endang (Babali Publisher, 2024)
Background: Chemotherapy is typically administered in specific doses and schedules to maximize its effectiveness in killing cancer cells. If a patient does not adhere to the prescribed regimen, the treatment may be less effective, potentially allowing the cancer to grow or spread. Digital interventions offer innovative approaches to address the issue of adherence. The aim of this study is to analyze the effect of digital interventions on enhancing cancer patients' adherence to chemotherapy. Method: This systematic review analyzed full-text original articles published in English in databases including Scopus, PubMed, Web of Science, CINAHL, and ProQuest from 2018 to February 2024. The articles were identified using the keywords: (telehealth OR telecare OR telenursing OR “smart application” OR “mobile application”) AND (adherence OR “treatment adherence”) AND (chemotherapy OR “adjuvant chemotherapy” OR “drug therapy”) AND (cancer OR neoplasm*). Bias was assessed using the Critical Appraisal Skills Program (CASP) tool. Results: A total of 456 items were found. Thirteen relevant papers from the literature search focused on breast cancer patients. The number of participants across all studies was 2,289. The digital interventions used included mobile games, video conferences, text messaging related to mobile health, and apps. These interventions provided medication reminders, symptom reporting, adherence tracking, and patient education, all of which contributed to increased chemotherapy adherence. Conclusion: Digital interventions positively influence chemotherapy adherence in cancer patients. The use of technology enables patients to actively participate in their treatment. This review was conducted across various continents, making the findings applicable to diverse ethnicities and races.